Low ketolytic enzyme levels in tumors predict ketogenic diet responses in cancer cell lines in vitro and in vivo - Zhang, Jie; Jia, Ping-Ping; Liu, Qing-Le; Cong, Ming-Hua; Gao, Yun; Shi, Han-Ping; Yu, Wei-Nan; Miao, Ming-Yong (Journal of lipid research, 2018)
The ketogenic diet (KD) is a high-fat, very-low-carbohydrate diet that triggers a fasting state by decreasing glucose and increasing ketone bodies, such as β-hydroxybutyrate (βHB). In experimental models and clinical trials, the KD has shown anti-tumor effects, possibly by reducing energy supplies to cells, which damage the tumor microenvironment and inhibit tumor growth. Here, we determined expression levels of genes encoding the ketolytic enzymes 3-hydroxybutyrate dehydrogenase 1 (BDH1) and succinyl-CoA: 3-oxoacid CoA transferase 1 (OXCT1) in 33 human cancer cell lines. We then selected two representative lines, HeLa and PANC-1, for in vivo examination of KD sensitivity in tumors with high or low expression, respectively, of these two enzymes. In mice with HeLa xenografts, the KD increased tumor growth and mouse survival decreased, possibly because these tumors actively consumed ketone bodies as an energy source. Conversely, the KD significantly inhibited growth of PANC-1 xenograft tumors. βHB added to each cell culture significantly increased proliferation of HeLa cells, but not PANCI-1 cells. Downregulation of both BDH1 and OXCT1 rendered HeLa cells sensitive to the KD in vitro and in vivo. Tumors with low ketolytic enzyme expression may be unable to metabolize ketone bodies, thus predicting a better response to KD therapy.